Demotivation in learning English among pre-university students in the ESL classroom / Nadhrah Fauzi - Fauzi, Nadhrah (2014)
English language performance of Malaysian students is still below satisfactory level and many studies have been conducted to investigate the factors. Research indicates that demotivation is one of the major factors of language learning failure in many ESL classrooms. The problem is that despite the link between demotivation and language learning failure, very little is known about this phenomenon. The purpose of this study is to examine the extent to which demotivating factors discourage the students in learning English in the ESL classroom. This study employed a primarily quantitative research design and utilized questionnaire together with a semi-structured interview. A total of 120 Pre-University students from a private university in Selangor were involved in this study. Findings revealed that students had been demotivated to a greater or lesser extent, most on several occasions and it was found that the most negative demotivating factor was Learners' Attitude towards learning English. A significant difference was found between male and female students with regards to Learning Environment and Implementation of lesson. The results also revealed that students, teachers, and institutions should play their vital role in developing more effective strategies to prevent ESL learners from being discouraged in learning English language. It is hoped that the study can contribute to the body of knowledge related to education towards minimizing demotivation among ESL learners.